Oscillator strengths for high-excitation Ti ii from laboratory measurements and calculations. Issue 1 (21st April 2016) - Lundberg, H.; Hartman, H.; Engström, L.; Nilsson, H.; Persson, A.; Palmeri, P.; Quinet, P.; Fivet, V.; Malcheva, G.; Blagoev, K.
Abstract: This work reports new experimental radiative lifetimes of six 3d 2 ( 3 F)5s levels in singly ionized titanium, with an energy around 63 000 cm −1 and four 3d 2 ( 3 F)4p odd parity levels where we confirm previous investigations. Combining the new 5s lifetimes with branching fractions measured previously by Pickering et al., we report 57 experimental log gf values for transitions from the 5s levels. The lifetime measurements are performed using time-resolved laser-induced fluorescence on ions produced by laser ablation. One- and two-step photon excitation is employed to reach the 4p and 5s levels, respectively. Theoretical calculations of the radiative lifetimes of the measured levels as well as of oscillator strengths for 3336 transitions from these levels are reported. The calculations are carried out by a pseudo-relativistic Hartree–Fock method taking into account core-polarization effects. The theoretical results are in a good agreement with the experiments and are needed for accurate abundance determinations in astronomical objects.